Quantitative Lipoproteomics in Clostridium difficile Reveals a Role for Lipoproteins in Sporulation. Issue 11 (19th November 2015) - Charlton, Thomas M.; Kovacs-Simon, Andrea; Michell, Stephen L.; Fairweather, Neil F.; Tate, Edward W.
Summary: Bacterial lipoproteins are surface exposed, anchored to the membrane by S -diacylglyceryl modification of the N-terminal cysteine thiol. They play important roles in many essential cellular processes and in bacterial pathogenesis. For example, Clostridium difficile is a Gram-positive anaerobe that causes severe gastrointestinal disease; however, its lipoproteome remains poorly characterized. Here we describe the application of metabolic tagging with alkyne-tagged lipid analogs, in combination with quantitative proteomics, to profile protein lipidation across diverse C. difficile strains and on inactivation of specific components of the lipoprotein biogenesis pathway. These studies provide the first comprehensive map of the C. difficile lipoproteome, demonstrate the existence of two active lipoprotein signal peptidases, and provide insights into lipoprotein function, implicating the lipoproteome in transmission of this pathogen. Graphical Abstract: Highlights: Alkyne-tagged myristate is an efficient probe for C. difficile lipoproteins Quantitative chemical proteomics enables lipoproteome profiling in diverse strains Chemical and genetic inactivation demonstrated the activity of an accessory LspA A vital role for the lipoproteome in sporulation has been identified Abstract : Bacterial lipoproteins are S -diacylglyceryl modified, surface anchored proteins, which play important roles at the host-pathogen interface. We use metabolic tagging, combined with inactivation of lipoprotein biosynthesis, to profile the Clostridium difficile lipoproteome, revealing a role for lipoproteins in transmission of this pathogen.